Análisis de los elementos del costo de la producción del maíz en el barrio Samilpamba, en la Parroquia Tanicuchi del Cantón Latacunga en el período septiembre 2017-febrero 2018 - Altamirano Taipe, Erika Viviana (2019)
The purpose of this project was to analyze the cost elements of corn production between two farmers in the Samilpamba neighborhood, by means of a previous contextualization of the grain production costs, which helped to determine which elements were into the crop, through a descriptive and field research, the information was collected through an producers’ interview and a check list, about each of the inputs, materials and services involved in the stages of cultivation. For the application of the same, a typology was made dividing the farmers into two groups: technical and not technical management in relation to the cultivation process. Once the production cost was established, by means of the process cost system based on the cost elements and the phenological phases of the two farmers cultivation, a comparison was made, and the different variations that exist and affect the cost were determined at the end. Finally the elements were established of the cost of corn crop and its real cost when sowing a hectare and how they vary depending on the circumstances of each farmer.